Hebrew for biblical interpretation - Walker-Jones, Arthur (Resources for biblical study, 2003)
Hebrew for Biblical Interpretation introduces elementary Hebrew with a focus on the skills needed for informed biblical exegesis. This innovative textbook, which combines the features of a traditional grammar with the insights of language education from applied linguistics, offers clear and concise discussions of grammatical concepts as well as guided exercises in reading and interpreting the Hebrew Bible. All words occurring more than 100 times in the Hebrew Bible are taught in descending order of frequency, and attention to grammatical clues reduces the need for rote memorization of paradigms. The integration of grammar and exegesis motivates students and makes this textbook well suited to seminary and undergraduate courses in which scholarly biblical exegesis is the primary goal of language acquisition.